Analisis Overload Transformator Distribusi pada Gardu PD0681 di PT PLN (Persero) ULP Ampera - Bersiap Ginting; Yessi Marniati; Ariqah Rafila Putri (Jurnal Ragam Pengabdian, 2026)
The distribution transformer at PD0681 substation of PT PLN (Persero) ULP Ampera experienced an overload condition that could accelerate insulation aging and reduce the reliability of the electrical distribution system. This study aimed to analyze the transformer loading during peak load conditions and determine an appropriate solution based on SPLN No. 50 of 1997. The analysis was carried out using field measurements of current and voltage on each phase. The results showed that the transformer loading reached 105.74% of its rated capacity of 100 kVA, indicating an overload condition. As a solution, an uprating simulation was performed by increasing the transformer capacity to 160 KVA, which reduced the loading level to 66.09%, placing it within the safe operating range. In addition, load growth was projected using the Least Square method, showing that the transformer loading would reach 76.11% in 2030, which is still within the acceptable operating limit according to the applicable standard. Therefore, transformer uprating is considered an effective technical solution to improve the reliability and continuity of long-term power distribution.